Cocrmo Alloy Treated by Floating Potential Plasma Assisted Nitriding and Plasma Based Ion Implantation: Influence of the Hydrogen Content and of the Ion Energy on the Nitrogen Incorporation - Pichon, L.; Okur, Salih; Öztürk, Orhan; Öztürk, Orhan; Okur, Salih; Rivière, J. P.; Drouet, M. (Elsevier Ltd., 2010)
Nitriding was performed on a medical grade CoCrMo alloy at 400°C in N2 or N2-H2 atmosphere at a working pressure of 0.84Pa for 2h. Various surface treatment techniques were used to incorporate nitrogen into the CoCrMo alloy: without any plasma assistance, by floating potential radio-frequency plasma assisted nitriding (FPPAN), by plasma based ion implantation (PBII) with several high voltage accelerations (up to 20kV). Without plasma activation, no nitrogen is incorporated in the CoCrMo. On the contrary, all the plasma or PBII treated samples show the formation of a nitrogen-rich f.c.c. γN phase. The layer nitrided over few microns has a nitrogen composition ranging from 30at.% to about 20at.% near the nitrided layer-substrate interface, with an enhanced surface microhardness. Hydrogen is found to enhance the nitriding efficiency. Without hydrogen, a high voltage polarization provides a supplementary amount of implanted nitrogen available for further diffusion and the sputtering of the surface passive oxide. So, with limited high voltages, thicker layers with higher amounts of nitrogen can be achieved by PBII compared to plasma nitriding. However, with higher voltages, the sputtering becomes too important and the nitride layer is thinner. © 2010 Elsevier B.V.
Keywords: Nitrogen plasma; Expanded austenite structure; Plasma based ion implantation; Wear resistance; Molybdenum alloys; Cobalt alloys